Pengaruh Pemberian Responsible Terhadap Minat dan Hasil Belajar Siswa Villain Pada Pembelajaran Fisika Kelas Xi Ipa 1 Madrasah Aliyah Syekh Yusuf - Tahir, Fadliana; Ali, Mukti; Khuzaimah, Andi Ulfah (Al-Khazini: Jurnal Pendidikan Fisika, 2021)
This study aims to determine whether thegiving of responsible affects the interest and learning outcomes of villain students in learning physics class XI IPA 1 Madrasah Aliyah Syekh Yusuf. This type of research is a single-subject experimental research using the A-B design. This study only usesone student as the research subject, and students who are the subject are students in the villain category (naughty). Students who are classified as villains are obtained from the criteria listed in several instruments used such as interview guidelines and sociometry to get subjects with the villain category. Based on the results of the analysis with descriptive analysis using graphical analysis, the average percentage of interest and learning outcomes for the baseline phase is 26.5% and 59.9%. Meanwhile, the average percentage of interest and learning outcomes for the intervention phase was 92.5% and 86.5%. It can be seen that the average in the baseline phase, namely the conditions that have not implemented the treatment in the form of providing responsibly for student interest and learning outcomes is very low compared to the intervention phase, namely the conditions for giving responsibility. So it can be concluded that responsible giving affects the interest and learning outcomes of villain students